Impact of EFL teachers' job satisfaction and their introversion/extroversion towards their instructional strategy use - Kafipour, Reza; Noordin, Nooreen (Innovare Academics Sciences, 2020)
In teaching and learning a second or foreign language, individual differences and affective factors have recently received great importance and attention from psychological and pedagogical point of views. Accordingly, the current research attempted to explore the impact of extroversion and introversion as personal traits on job satisfaction among Iranian English as foreign language learners (EFL). Apart from that, the study also attempted to clarify the impact of these factors on EFL teachers' instructional strategy use through teaching L2 and classroom activities. Eighty EFL learners were selected as the participants for the study. In collecting the data, three instruments were utilized: a personality questionnaire, job satisfaction questionnaire and strategy inventory for language learning. The collected data were scored, classified, and interpreted by Statistical Package for Social Sciences (SPSS) software. The obtained statistical results were reported in three sections. Firstly, the findings revealed that introvert Iranian EFL teachers were more satisfied than their extrovert counterparts even though this difference was not statistically significant. Secondly, the EFL teachers were more satisfied with the use of“Memory Strategy ” as an instructional strategy in their teaching. On the other hand, they were least satisfied with the “Social Strategy” as an instructional strategy in teaching. Finally, as indicated in the results obtained, EFL teachers with different levels of job satisfaction did not utilize different types of instructional strategies as expected. In other words, there was no statistically significant correlation between the level of job satisfaction and teachers’ instructional strategy use.